TINGKAT BIOKONSENTRASI LOGAM BERAT DAN GAMBARAN HISTOPATOLOGI IKAN MUJAIR (Oreochromis Mossambicus) YANG HIDUP DI PERAIRAN TUKAD BADUNG KOTA DENPASAR - Made Rahayu Kusumadewi; I Wayan Budiarsa Suyasa; I Ketut Berata (Master Program of Environmental Science, Postgraduate Program of Udayana University, 2015)
Tukad Badung River is one of the potential contamination of heavy metal sare very highin the city of Denpasar. Tilapia (Oreochromis mossambicus) isa commonspecies of fish found in the river and became the object of fishing by the public. The fish is usually consume das a food ingredient forever yangler. Fish can be used as bio-indicators of chemical contamination in the aquatic environment. Determination of heavy metal bioconcentration and analysis of liver histopathology gills organs and muscles is performed to determine the content of heavy metals Pb, Cd, and Cr+6, and the influence of heavy metal exposure to changes in organ histopathology Tilapia that live in Tukad Badung. In this observational study examined the levels of heavy metal contamination include Pb, Cd and Cr+6 in Tilapia meat with AAS method (Atomic Absorption Spectrofotometric), and observe the histopathological changes in organ preparations gills, liver, and muscle were stained with HE staining (hematoxylin eosin). Low Pb content of the fish that live in Tukad Badung 0.8385 mg/kg and high of 20.2600 mg/kg. The content of heavy metals Pb is above the quality standards specified in ISO 7378 : 2009 in the amount of 0.3 mg / kg. The content of Cr+6 low of 1.1402 mg / kg and the highest Cr+6 is 6.2214 mg / kg. The content of Cr+6 is above the quality standards established in the FAO Fish Circular 764 is equal to 1.0 mg / kg. In fish with Pb bioconcentration of 0.8385 mg / kg and Cr+6 of 1.1402 mg / kg was found that histopathological changes gill hyperplasia and fusion, the liver was found degeneration, necrosis, and fibrosis, and in muscle atrophy found. Histopathologicalchangessuch asedema and necrosis ofthe liveris foundin fishwith Pb bioconcentration of 4.5225mg/kg and Cr+6 amounted to2.5163mg/kg. Bio concentration of heavy metal contamination of lead (Pb) and hexavalent chromium (Cr+6) on Tilapia ( Oreochromis mossambicus ) who lives in Tukad Badung river waters exceed the applicable standard. Histopathological changes occur in organs gills, liver, and muscle as a result of exposure to heavy metals lead and hexavalent chromium. Advised the people not to eat Tilapia that live in Tukad Badung